1989
DOI: 10.1007/bf01799677
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plasma valine, isoleucine and leucine on the control of the flux through tyrosine‐ and tryptophan‐hydroxylase in the brain

Abstract: The effect of increasing blood levels of valine, isoleucine and leucine on the fluxes through tyrosine and tryptophan hydroxylase in brain has been calculated and analysed in terms of flux control coefficients. It is concluded that any beneficial effect of increasing the concentration of these amino acids in phenylketonuria patients is not due to a decrease in brain phenylalanine or an improved neurotransmitter synthesis through tyrosine or tryptophan hydroxylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…[41] Regarding the latter hypothesis, besides brain Phe levels, especially brain monoaminergic neurotransmitters have been suggested to be important for neurocognitive and psychosocial outcome of PKU patients [17,42,43]. Data of our study show that the relation between plasma Phe and brain Phe was stronger than the relation between plasma Phe and brain neurotransmitters, suggesting that the pathogenesis of decreased neurotransmitters is not only based on Phe toxicity, but could in addition be due to the inhibition of the influx of the precursors of the dopamine and serotonin pathway or the direct inhibition of brain Phe on Tyr and Trp hydroxylase activities [44][45][46].…”
Section: Discussionmentioning
confidence: 61%
“…[41] Regarding the latter hypothesis, besides brain Phe levels, especially brain monoaminergic neurotransmitters have been suggested to be important for neurocognitive and psychosocial outcome of PKU patients [17,42,43]. Data of our study show that the relation between plasma Phe and brain Phe was stronger than the relation between plasma Phe and brain neurotransmitters, suggesting that the pathogenesis of decreased neurotransmitters is not only based on Phe toxicity, but could in addition be due to the inhibition of the influx of the precursors of the dopamine and serotonin pathway or the direct inhibition of brain Phe on Tyr and Trp hydroxylase activities [44][45][46].…”
Section: Discussionmentioning
confidence: 61%
“…In those studies it was concluded that effects at the BBB could not provide an entire explanation for the aetiology of brain damage, since similar Completion effects take place in histidinaemia and tyrosinaemia, type II, where brain dysfunction does not develop to the same extent. Further, the effects of elevating plasma levels of valine, isoleucine and leucine were theoretically considered, and the authors found that brain phenylalanine levels were relatively unaffected by increasing levels of these competing amino acids (Hommes and Lee 1990b). In all three studies, however, older K m values for the transport of large neutral amino acids at the rat BBB were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, phenylalanine concentrations were significantly higher in salivary samples of pSS patients in previous studies, which were analyzed by H-NMR pectroscopy [ 25 ]. Phenylalanine hydroxylation to tyrosine, which can synthesize important neurotransmitters and hormones, is carried out by phenylalanine hydroxylase [ 30 ]. In recent studies, proteomic analysis revealed that tyrosine-protein phosphatase nonreceptor type 6 (PTPN6) was dysregulated in saliva and salivary glands in pSS murine models [ 31 ].…”
Section: Discussionmentioning
confidence: 99%